One stage repair for an oesophageal fistula after pneumonectomy using an omental pedicle flap. Issue 11 (November 1988) - Asaoka, M; Imaizumi, M; Kajita, M; Uchida, T; Niimi, T; Abe, T
Abstract : A 67 year old man developed an oesophageal fistula after a pneumonectomy that was complicated by an empyema. An omental pedicle flap was brought through the diaphragm to repair the fistula and to fill the empyema space. The outcome was successful.